ANALISIS KAFEIN DALAM KOPI BUBUK DI KOTA MANADO MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Maramis, Rialita Kesia (PHARMACON, 2013)
Caffeine is one of alkaloids which contains in coffee bean, tea leaves and cacao bean. Theaims of this research were to determine caffeine level in coffee powder and the maximum ofcoffee powder level which consumed per day based on SNI. Samples were 6 coffee powdersin Manado city. Identification of caffeine was done using parry reagent, although caffeinelevel was determine using spectrophotometer UV-Vis. The result shows that 6 coffeepowders from Manado contained caffeine. Caffeine level in Manado coffee powder were13,81 mg (sample A), 13,63 mg (sample B), 12,33 mg (sample C), 10,10 mg (sample D),10,13 mg (sample E) and 9,53 mg (sample F). Maximum coffee powder level whichconsumed per day based on SNI were 15,73 g-10,86 g per day.Key words : Caffeine, coffee powder, spectrophotometry UV-Vis, Manado